Standards of Criminal Procedure Evidence - VAPNIARCHUK, Viacheslav V.; TROFYMENKO, Volodymyr M.; SHYLO, Olha G.; MARYNIV, Volodymyr I. (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
The strategy of integration development of Ukraine envisages, in particular, the implementation of international standards of justice in the legal system of Ukraine. The article explores the essence of such a legal category as ‘the standard of criminal procedural proof’. The rules of evidence in the Anglo-Saxon and continental legal systems in the context of this issue are analyzed, as well as domestic criminal procedural legislation on the peculiarities of assessment of evidence in various criminal proceedings and at various stages. Conclusions are made on the existence of objective evidence of standards in the Anglo-Saxon family of law (‘beyond reasonable doubt’ and ‘probability balance’) and the subjective standard of proof in the countries of the continental system of law (‘on the basis of internal conviction’). The opinion on the lawfulness and expediency of the allocation of certain objective standards of proof and in domestic criminal proceedings is expressed.